ANALISIS PROGRAM PENINGKATAN DAN PENGEMBANGAN PRODUKTIVITAS SEKTOR PERTANIAN DI KECAMATAN CIBINGBIN KABUPATEN KUNINGAN - Jajang Cahyadiana; Lalas Sulastri (JRPA - Journal of Regional Public Administration, 2019)
About the research that the author is doing is to get an overview of the implementation of the Productivity and Agricultural Sector Productivity Program Improvement Program in Cibingbin District, Kuningan Regency, the weaknesses of the implementation of the Productivity and Agriculture Sector Productivity Development Program in Cibingbin District, Kuningan Regency, and efforts to overcome the Program policies Increasing and Developing Agriculture Sector Productivity in Cibingbin District, Kuningan Regency. The method used in this study is a qualitative research method with independent variables, namely: Implementation of Productivity and Agricultural Sector Productivity Development Programs. The sampling technique used was purposive sampling, namely the sampling technique for data sources with certain considerations. The data / information sources are: A Head of PTP3 UPTD, a Head of PTP3 UPTD Subdivision, 2 PTP3 UPTD POPTs and 1 PTP3 UPTD Executor. Whereas in analyzing the data used the Miles and Huberman Model with steps: data reduction, data presentation, concentration drawing / verification and Triangulation. Based on the results of interviews and data analysis, it was concluded that the Implementation of the Productivity and Agricultural Sector Productivity Development Program in Cibingbin District was quite good, although there were still indicators that still needed improvements in its implementation. Factors influencing the Implementation of Productivity and Agricultural Sector Productivity Development Program in Cibingbin District, Kuningan Regency, namely: Environmental conditions, Relations between organizations, Resources for program implementation and Characteristics and female agent implementation. Efforts to improve the implementation of the Productivity and Agriculture Sector Productivity and Development Program in Cibingbin District, Kuningan Regency, include: a tiered revision of the policy mismatch, information dissemination in the form of socialization, holding a training or coaching gradually for PTT3 UPTD staff and then applied to farmer groups. through an intensification campaign, and maximizing existing facilities and proposing additional facilities to the central Government